THE IMPACT OF FINANCIAL BALANCE ON FINANCIAL HEALTH (AN ANALYTICAL STUDY OF A SAMPLE OF COMMERCIAL BANKS LISTED ON THE IRAQI STOCK EXCHANGE FOR THE PERIOD (2013-2022) - Khaled Abdullah Khader Al-Tai; Nisreen Muhammad Taher Saadi (Scholar Express Journals, 2024)
The research aims to test the impact of financial balance on the financial health of Iraqi commercial banks, using a sample of (9) commercial banks listed on the Iraqi Stock Exchange (2013-2022). Three financial indicators were chosen to measure financial balance: (liquidity index, Financial flexibility, water solvency index), and financial health was measured through (rate of return on assets). The descriptive and analytical approach was used for the data and information contained in the financial reports of the banks in the research sample. Ready-made software was also used, including (MS Excel) and (Eviews 13) ), to test hypotheses and answer questions related to the research problem and reach the goals, and the research reached a set of results, the most important of which are: The banks in the research sample do not suffer from a financial imbalance resulting from weakness in its three dimensions. The research also presented a set of recommendations, the most important of which are: the need for banks to evaluate... Monitoring its financial performance on an ongoing basis, using financial health indicators due to their importance in the strength of the financial position of any bank.
Keywords: financial balance; financial health; commercial banks